Cornel Iridoid Glycoside Protects Against STAT1-Dependent Synapse and Memory Deficits by Increasing N-Methyl-D-aspartate Receptor Expression in a Tau Transgenic Mice - Ma, Denglei; Huang, Rui; Guo, Kaiwen; Zhao, Zirun; Wei, Weipeng; Gu, Lihong; Li, Lin; Zhang, Lan (Frontiers in Aging Neuroscience, 2021)
P301S transgenic mice is an animal model of tauopathy and Alzheimer’s disease (AD), exhibiting tau pathology and synaptic dysfunction. Cornel iridoid glycoside (CIG) is an active ingredient extracted from Cornus officinalis, a traditional Chinese herb. The purpose of the present study was to investigate the effects and mechanisms of CIG on tau pathology and synaptic dysfunction using P301S mice. Intragastric administration of CIG for 3.5 months improved learning and memory abilities, increased the survival rate of P301S mice. Electrophysiological recordings and transmission Electron microscopy study showed that CIG improved synaptic plasticity, increased the ultrastructure and number of synapse. Moreover, CIG increased the expression of N-methyl-D-aspartate receptors (NMDARs) subunits GluN1, GluN2A and GluN2B, α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluA1. The major mechanism of CIG involved in the regulation of synaptic dysfunction was inhibiting the activation of Janus kinase-2 (JAK2) /signal transducer and activator of transcription 1 (STAT1) signaling pathway, and alleviating STAT1-induced suppression of NMDAR expressions. Based on our findings, CIG might be a promising candidate for the prevention of tauopathy such as AD.